2016
DOI: 10.1038/bmt.2016.107
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic status with autologous hematopoietic cell transplantation outcomes for lymphoma

Abstract: Socioeconomic status (SES) is an important determinant of disparities in health care. The association of SES with outcomes in autologous hematopoietic cell transplantation (AHCT) has not been described previously. We conducted a retrospective cohort study of 687 AHCT recipients with lymphoma transplanted between 2003 and 2013. Patients were categorized into low (<$50 000/year) and high SES (⩾$50 000/year). A greater proportion of low SES patients lived farther away from our center (median 54 vs 28 miles), belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…As noted previously, most previous studies have shown no impact of long driving distances or rural residences on clinical outcomes after HCT [32,34,[37][38][39][40][41][42]. Our study adds to this literature by investigating driving distance and patient-reported outcomes after HCT.…”
Section: Impacts Of Driving Distance On Hct Survivorshipsupporting
confidence: 60%
See 1 more Smart Citation
“…As noted previously, most previous studies have shown no impact of long driving distances or rural residences on clinical outcomes after HCT [32,34,[37][38][39][40][41][42]. Our study adds to this literature by investigating driving distance and patient-reported outcomes after HCT.…”
Section: Impacts Of Driving Distance On Hct Survivorshipsupporting
confidence: 60%
“…Multiple centers have retrospectively investigated whether long driving distances or rural residences affect overall survival after HCT [ 32 , 34 , 37 , 38 , 39 , 40 , 41 , 42 ]. Although these studies have generally reported no impact of driving distances on clinical outcomes, the impact of driving distances on patient-reported outcomes (PROs) after HCT is unknown.…”
mentioning
confidence: 99%
“…In a population-based study among 6,234 patients in Denmark diagnosed with NHL in 2000–2008, all-cause mortality was increased by 63% for patients with a short education compared with patients with higher education, and there was a significant higher frequency of intensive treatment in patients with higher education 11. In line with these findings, Hong et al showed in a retrospective single-center study among 687 patients with NHL in Ohio that a high socioeconomic position was associated with a significantly better OS (HR 0.74, 95% CI: 0.58–0.95) 12. Investigations of the impact of socioeconomic factors on treatment intensity in the relapse setting are scarce.…”
Section: Introductionmentioning
confidence: 79%
“…At a median total healthcare cost at 100 days of $289,283 for the myeloablative HSCT and $253,467 for reduced-intensity HSCT (39), allogeneic HSCT is not a viable treatment option for the nearly 37 million PLWH globally. This reason alone has weakened support of HSCT as a viable strategy for HIV cure (40)(41)(42)(43). More recently, the use of virally transduced chimeric antigen presenting autologous T-cells (CAR-T) has broadened the potential utility of immune directed anticancer therapy with approval of several agents in this class by the US FDA for the treatment of refractory leukemia and lymphoma (44).…”
Section: Hematopoietic Stem Cell Transplantation and Cellular Therapymentioning
confidence: 99%